2019
DOI: 10.21203/rs.2.11697/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Body mass index and lifetime healthcare utilization

Abstract: Background: Overweight and obesity is a major global public health challenge, and understanding the implications for healthcare systems is essential for policy planning. Past studies have typically found positive associations between obesity and healthcare utilization, but these studies have not taken into consideration that obesity is also associated with early mortality. We examined associations between body mass index (BMI, reported as kg/m2) and healthcare utilization with and without taking BMI-specific s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(39 reference statements)
1
5
0
1
Order By: Relevance
“…40,[51][52][53][54][55][56] In addition, the patterns we identified align with previous research: that costs peak late in life (at 60-70 y old) 23,40,54 and are higher among women than men. 23,[53][54][55] Generally, cost estimates vary substantially between studies. 53 Since different studies use different data sources, it is hard to disentangle how much of this variation is caused by differences in the analytical frameworks applied or the populations under analysis.…”
Section: Discussionsupporting
confidence: 87%
“…40,[51][52][53][54][55][56] In addition, the patterns we identified align with previous research: that costs peak late in life (at 60-70 y old) 23,40,54 and are higher among women than men. 23,[53][54][55] Generally, cost estimates vary substantially between studies. 53 Since different studies use different data sources, it is hard to disentangle how much of this variation is caused by differences in the analytical frameworks applied or the populations under analysis.…”
Section: Discussionsupporting
confidence: 87%
“…The risk of stroke is increased fivefold in patients with nonvalvular AF (NVAF), and strokes are more likely to be severe in NVAF patients [2]. Obesity is a worsening public health crisis associated with serious health consequences, challenges for healthcare providers, and substantial economic burden [3][4][5]. The prevalence of adult obesity in the US was estimated at 42% in 2017-2018 and may approach 50% by 2030 [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study using the 2001-2016 Medical Expenditure Panel Survey found that total direct medical costs of obesity in US adults doubled from 2001 ($124.2 billion) to 2016 ($260.6 billion), and total annual medical expenditures of obese adults ($5010) were double those of people of normal weight ($2504) [17]. Overweight and obese individuals have increased utilization of primary and secondary healthcare services compared with those of normal body weight [2,17,18]. In addition, obese individuals are prescribed nearly twice as many medications and are nearly four times more likely to be hospitalized compared with nonobese individuals [2].…”
Section: Introductionmentioning
confidence: 99%